Company Value: Dividend Policy, Share Ownership Structure, and Asset Structure Mediated with Capital Structure (Case Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period) - Jaka Paksilodra; Erny Amriani Asmin; Chandra Ayu Pramestidewi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to analyze and determine the effect of Dividend Policy, Share Ownership Structure, and Asset Structure on Company Value with Capital Structure as an Mediating variable in Food and Beverage sector companies listed on the Indonesia Stock Exchange during the period of 2021-2023. The data processing in this study uses quantitative data analysis and employs SPSS 25 (Statistical Package for Social Science). The sample in this study consists of 30 Food and Beverage sector companies listed on the Indonesia Stock Exchange during the period of 2021-2023. The results show that Dividend Policy and Share Ownership Structure have a negative and significant impact on capital structure, while Asset Structure has a positive and significant impact on capital structure. Dividend Policy and Share Ownership Structure have a positive and significant impact on company value, while Asset Structure has a negative impact and is significant to firm value, while Asset Structure has a negative and significant effect on firm value. Capital Structure can mediate the relationship between Dividend Policy, Share Ownership Structure (Public Ownership), and Asset Structure on Firm Value.